A Comparative Analysis of Zernike and Karhunen-Loeve Polynomials for Wave-front Correction in Modal Adaptive Optics Systems - Hassan, Raaid Nawfee (Iraqi Journal of Science, 2026)
This work employed the Zernike and Karhunen-Loeve polynomials in the adaptive optics (AO) systems to correct wave-front aberrations. The present work uses MATLAB-based program for simulating wave-front distortion correction with the use of the Modal AO method. Wave-front aberrations were represented by a modified von Karman turbulence model; numerical simulations and analyses were performed. The Zernike polynomials higher values of SNR and Strehl ratios, lower values of RMSE, variance, and covariance in comparison to Karhunen-Loeve polynomials modes, proved the superiority of the Zernike polynomials in correcting wave-front distortion. The present work provides valuable insights into the quality and performance metrics of the Karhunen-Loeve and Zernike modes, with a focus on gaining a more detailed understanding of the different aberration modes for enhancing wave-front corrections in optical systems.